A brief treatment for veterans with PTSD: an open-label case-series study - Kindt, Merel; Soeter, Marieke (Frontiers in Psychiatry, 2023)
Introduction Despite the positive outcomes observed in numerous individuals undergoing trauma-focused psychotherapy for PTSD, veterans with this condition experience notably diminished advantages from such therapeutic interventions in comparison to non-military populations. Methods In a preliminary study we investigated the efficacy of an innovative treatment approach in a small sample of veterans (n = 7). Recognizing that accessing and targeting trauma memory in veterans with PTSD may be more challenging compared to other patient populations, we employed unique and personalized retrieval cues that engaged multiple senses and were connected to the context of their trauma. This was followed by a session focused on memory reconsolidation, which incorporated both psychological techniques (i.e., imagery rescripting) and a pharmacological component (i.e., 40 mg of propranolol). Results The findings from this small-scale case series cautiously indicate that this brief intervention, typically consisting of only one or two treatment sessions, shows promise in producing significant effects on symptoms of PTSD, distress and quality of life.This is particularly noteworthy given the complex symptomatology experienced by the veterans in this study. Conclusion To summarize, there are grounds for optimism regarding this brief treatment of combat-related PTSD. It appears that the potential for positive outcomes is far greater than commonly believed, as demonstrated by the encouraging results of this pilot study.